Employee Motivation and Commitment Among Senior High School Teachers in Urdaneta City National High School - Samera, Norman (Journal of Research and Investigation in Education, 2025)
The purpose of this study is to look into the level of organizational motivation and commitment, as well as the relationship between motivation and organizational commitment, in the Urdaneta City National High School. The relationships between organizational motivation and commitment were investigated using different methodologies and statistical tools. A total of 22 respondents participated in the research survey. A questionnaire was used to collect data for this study. The "Motivation Questionnaire" and the "Organizational Commitment Questionnaire" were administered to senior high school teachers. Within this scope, teachers' motivation levels were examined in two dimensions: intrinsic and extrinsic motivation; and teachers' organizational commitment levels were examined in three dimensions: affective commitment (AC), continuance commitment (CC), and normative commitment (NC). The results showed that there is a significant impact of employee motivation on organizational commitment. Important recommendations are also derived from the study.